2004
DOI: 10.1007/s00383-003-1053-y
|View full text |Cite
|
Sign up to set email alerts
|

The herbal medicine Rikkunshi-to stimulates and coordinates the gastric myoelectric activity in post-operative dyspeptic children after gastrointestinal surgery

Abstract: Rikkunshi-to (TJ-43), a gastroprotective herbal medicine, has been used for the symptomatic relief of adult patients with dyspepsia. However, its mechanism has yet to be fully elucidated. The aim of this study is to evaluate the effect of TJ-43 on the gastric myoelectric activity in post-operative dyspeptic patients, whose symptoms persisted for over 1 year after gastrointestinal surgery. Electrogastrography (EGG) recordings were performed to calculate the biomechanical parameters on the dominant peak frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 22 publications
1
45
0
Order By: Relevance
“…Previously, the acceleration of gastric emptying (1, 10), the increase in plasma somatostatin and gastrin levels (11), and the stimulation of gastric myoelectric activity after gastrointestinal surgery (12) were reported as clinical effects of Rikkunshi-to. On the other hand, some basic studies have demonstrated that Rikkunshi-to prevents gastric mucosal damage (13,14) and recovers the gastric adaptive relaxation (GAR) abolished by treatment with L-NNA in the isolated guinea pig stomach (15).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the acceleration of gastric emptying (1, 10), the increase in plasma somatostatin and gastrin levels (11), and the stimulation of gastric myoelectric activity after gastrointestinal surgery (12) were reported as clinical effects of Rikkunshi-to. On the other hand, some basic studies have demonstrated that Rikkunshi-to prevents gastric mucosal damage (13,14) and recovers the gastric adaptive relaxation (GAR) abolished by treatment with L-NNA in the isolated guinea pig stomach (15).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, it has been reported that rikkunshito improves gastrointestinal complaints related to functional dyspepsia (47,51), and its efficacy has been proven in a multicenter double-blind study (17). Recently, it has also been reported that rikkunshito leads to a fundamental and clinical reduction in esophageal acid reflux and related symptoms in patients with GERD (21)(22)(23)32).…”
mentioning
confidence: 99%
“…Rikkunshito is an orally administered Japanese herbal (Kampo) preparation that is widely prescribed for patients showing various gastrointestinal symptoms such as gastroesophageal reflux (5,6), dyspeptic symptoms of post gastrointestinal surgery (7,8), and chemotherapy-induced nausea (9). Rikkunshito is composed of 8 constituents: Glycyrrhizae radix (4.7%), Zingiberis rhizoma (2.3%), Atractylodis lanceae rhizoma (18.6%), Zizyphi fructus (9.3%), Aurantii nobilis pericarpium (9.3%), Ginseng radix (18.6%), Pinelliae tuber (18.6%), and Hoelen (18.6%).…”
Section: Introductionmentioning
confidence: 99%